The Discontinuation Effect of Topical Prednisolone on Extracellular Matrix Trabecular Meshwork in Wistar Rat - Sekar Kumalasari; Liana Ekowati; Arief Wildan; Hermawan Istiadi; Arnila Novitasari Saubig; Fifin Luthfia Rahmi (Faculty of Medicine, Universitas Diponegoro, 2022)
ABSTRACT Background:Intra ocular pressure (IOP) elevationis one of topical steroids’ side effects. Corticosteroid will initiate matrix metalloproteinase cascade that leads to extra cellular matrix (ECM)of trabecular meshwork (TM) turnover(remodeling) and its acumulationin TM. Objective: To analyze the reversibility of ECM TM in Wistar rat after discontinuation oftopical prednisolone1% at different periode(14 days and 28 days). Methods:This was an experimental study with post test only controlgroup design. Total samples of 28 rats were divided into 4 groups: Treatment groups 1 was treated with topical prednisolone for 28 days, and was terminated 14 days after discontinuation of the drug.Treatment goups2 was treated topical prednisolone for 28 days and was terminated28 days after discontinuation of the drug. Control 1 was treated withtopical prednisolone for 28 days, and Control 2 was treated with topical saline for 28 days and terminated without periode of discontinuation. Histopathological grading score was used to evaluate ECM TM deposition. Mann-Whitney test and Kruskal-Wallis test were used to analyze the data. Result: Deposition of ECM in TM was not statistically different intreamentgroup 1 and treatment group 2 (p>0.05). Deposition of ECM in TM were statistically differentbetween treatment group 2 and control group 1 (p<0.05). Comparative test showed p<0.001,which means that there was a change in the thickness of ECM after discontinuation of instillation. Conclusion: ECM TM was thinner in the experimental animals with a longer duration of topical prednisolondiscontinuation, which demonstrate that maintenance remodeling of ECM was happen.